PERANAN SEKTOR INFORMAL DALAM MENJAGA KEBERSIHAN LINGKUNGAN DI DAYA TARIK WISATA PANTAI SANUR - Dwi Wawan Wira Buana; I Nyoman Sunarta (Program Studi Sarjana Pariwisata, Fakultas Pariwisata, Universitas Udayana, 2015)
ABSTRACT The background of this research was less clean than some trash coast caused by tourists themselves or garbage brought by coastal currents. In the presence of the informal sector in the coastal Sanur Beach is expected to contribute well to the coast of Sanur, with the obligation that is given from the manager of Sanur Beach (Bundes), which enjoined every merchant located in coastal Sanur Beach to keep clean and carry out activities related to the cleanliness. Based on the above research that revealed two problems, namely what the informal sector's role in keeping the environment in Sanur Beach? and the depth of the depth of the informal sector faced in keeping the environment in Sanur Beach? To express the above problem this research using primary and secondary data sources, while the type of data used is the qualitative data and quantitative data. With this method of data collection through observation, interviews, and library research. With data analysis. The results of this study indicate that the role of traders on the coast of Sanur have a positive impact on the cleanliness of the beach in Sanur with efforts that traders do, that Sanur Beach embodies clean, implementing sweeping, pewadahan, collection, and increase community participation in protecting the environment. Constraints faced by traders in Sanur Beach menunjng kebesihan ie, lack of hygiene group contained in Sanur beach, there are large trees, limited infrastructure, lack of tourist awareness, community participation, awarenesstourists.